Information design products in visual culture: university campuses - Karaalioğlu, Sevim (Istanbul Kultur Univ, Atakoy Campus, Bakirkoy, Istanbul, 34156, Turkey, 2015)
The study subject involves directional tools and aids found throughout university campuses. The objective of this study is to analyze the directional tools and aids via graphics and written communication, enable users to find their way easily around campus. This study will also contribute to overcoming problems encountered in this field. The model of the study is the scanning model which focuses on description. A survey of 21 questions prepared by the researcher was given to participants, and data was subsequently collected. The participants forming the study group were selected from the following four universities located in Ankara: Atilim University, Bilkent University, Gazi University's Glbasi Campus and Hacettepe University's Beytepe campus. 120 participants were selected from each university; participants were further divided into the following 4 categories: lecturers, students, administrative staff, or visitors. 30 participants were selected from each category for each university. Data from the surveys were calculated as percentages and frequencies determined using SPSS analysis software, and results of the analysis were discussed. As a result of this study, deficiencies in the campus have been identified and recommendations on improvement have been made. The directional tools and aids used within the campus should be compatible with the corporate identity. Furthermore, universities are required to have campus maps located throughout campus. In general, It has been determined that guiding signs found throughout university campuses are insufficient. Significant differences between user opinions in favor of private universities (Atilim-Bilkent).
Keywords: Graphic design; Information design; Corporate identity